MOTIF PUBLIK BERKONTRIBUSI DALAM RUBRIK JURNALISME WARGA KORAN HARIAN SOLOPOS TAHUN 2018 - Rahmadina, Vira (Komodifikasi, 2019)
Citizen journalism is a development of the journalistic world that allows consumers to create their own news media. The development is also adopted by Solopos through the rubric of Citizen Journalism. With their Rubric Citizen journalism is expected Solopos newspaper will be a public space as it has aspired by Habermas. Reality is what will be appointed by the researchers about how citizen journalist motivation in sending the news on Solopos daily newspaper as well as how the practice of public space on the rubric of citizen journalism Solopos daily newspaper. In this study, researchers used the theory proposed by Maslow's motivation as well as public spaces Jürgen Habermas's theory to analyze the problems researchers used a qualitative research method with descriptive approach. Data collection techniques with in-depth interviews and documentation. As for the sample using purposive sampling by taking six citizen journalistic criteria senders delivered news intents with the number of items of more than 25 news, was the shipment of 12-15 news and news rarely with 1-4 posts in one year. The second criterion is willing and capable of being informants of the study. Broadly speaking, the results of this study showed that of the five motivational hierarchy proposed by Maslow, there are two motivations citizen journalist in sending the news that the motive for rewards and motives of self-actualization.